Language Technologies for the Challenges of the Digital Age 27th International Conference, GSCL 2017, Berlin, Germany, September 13-14, 2017, Proceedings - Rehm, Georg; Declerck, Thierry (Lecture Notes in Artificial Intelligence, 2018)
semantics; artificial intelligence; natural language processing systems; natural language processing; NLP; machine learning; social networking; named entities; support vector machines; SVM